CD4 T-Cell Immunity in the Lung - Kolls, Jay K. (Mucosal Immunology of Acute Bacterial Pneumonia, 2012)
T helper cells are a distinct lineage of T-cells that can differentiate into the well-characterized subsets, Th1 and Th2 and a newer subset called Th17 cells. Data to date suggest that these cells play specific roles in host defense in the lung and thus, these subsets can also be targeted for vaccine-induced immunity. Here we summarize recent progress in our understanding of these specific T-cell subsets, their effector cytokines, and how these cells regulate host defense against pulmonary infection.